Evaluación de los Trastornos Musculoesqueléticos en docentes universitarios que teletrabajan en tiempos de Covid: Musculoskeletal Disorders Evaluation in teleworking university teachers during COVID times (La U Investiga, 2020)
The COVID-19 pandemic is one of the greatest challenges that societies and companies have faced, where to ensure the safety of people and the sustainability of companies and jobs, worldwide they have chosen by teleworking as a work alternative. The main objective of the research was to evaluate the musculoskeletal symptomatology in university teachers who carry out Telework in time of COVID-19. It is a quantitative,descriptive, and cross-sectional investigation, which was applied to 25 teachers who were with telework functions during the COVID-19 confinement stage, belonging to the Faculty of Health Sciences of the Technical University of North. Within the instruments, a sociodemographic record and the Nordic Questionnaire were applied. Among the main results, a predominance of the age range of 36-64 years was obtained, the majority being female. In the evaluation of musculoskeletal disorders in relation to theregion where they presented discomfort in the last 12 months, the neck predominated; according to the time of discomfort in the last 12 months according to anatomical regions, the predominant duration was 1-7 days represented in the neck region; In what corresponds to the duration of the episode, the majority was 1-24 hours, presented in the same way in the neck; finally, according to the note assigned to his complaints, apredominance of note 3 was evidenced, presented mainly on the shoulder.
Keywords: Musculoskeletal Disorders; COVID; telework; University Teachers